Peningkatan Hasil Belajar Siswa Menggunakan Model Team Games Tournament di Kelas V Sekolah Dasar - Edlis, Ummu Shiddiqah; Alwi, Nur Azmi (Universitas Negeri Padang, 2024)
Field observations are conducted as a result of the poor student learning results, which form the basis of this research's motivation. This study tries to clarify how Team Games Tournaments (TGT), a type of cooperative learning, enhance learning results. Classroom action research (PTK), which combines qualitative and quantitative methods, falls under this category. 26 pupils from class V SD Negeri 05 Padang Pasir Padang served as the research subjects. The outcomes revealed that the assessment of lesson plans for cycle I produced an average score of 83.32% (B), and the score for cycle II increased to 97.22% (SB). The average level of teacher involvement was 80.35% (B) in cycle I, increasing to 96.42% (SB) in cycle II. While student activity has an average value of 80.35% (B) in cycle I and increases to an average of 96.42% (SB) in cycle II. Based on this, the Team Games Tournament Cooperative Learning methodology can, thus, improve student's learning outcomes in class V at SD Negeri 05 Padang Pasir, Padang City, during integrated thematic learning